Risk assessment of morbidly obese parturient in cesarean section delivery: A prospective, cohort, single-center study. Issue 42 (October 2017) - An, Xiaohu; Zhao, Yanhong; Zhang, Ying; Yang, Qiling; Wang, Yilong; Cheng, Weiwei; Yang, Zeyong
Abstract: Background: Up to 40% of women gain excessive weight during pregnancy. Obesity complications and risks in parturient women undergoing cesarean section (CS) with different anesthetic methods remain unknown. This study aimed to assess the safety and risk of obese women undergoing CS delivery with various perioperative anesthetic methods. Methods: Seven hundred ninety parturient women underwent CS under general anesthesia (GA), intraspinal anesthesia including epidural anesthesia (EA) and combined spinal-epidural anesthesia (CSEA). They were divided into morbid (n = 255), severe (n = 274), and non-obesity (n = 261) groups. This study is registered with ClinicalTrials.gov (number NCT03002636). Result: Between 2013 and 2016, 790 pregnant were assessed. Compared with the non-obesity group, there were significantly more fetal distress and higher body mass index (BMI) in the morbid obesity group ( P = .0001 and P = .001, respectively). Significantly more patients showed preeclampsia, multifetation, amniotic fluid abnormality, and high bleeding amounts in the morbid obesity group compared with the non-obesity group ( P = .0001, P = .048, P = .017, and P = .018, respectively); more patients were administered EA and GA compared with the non-obesity group ( P = .0001 and P = .0001, respectively). More post-anesthesia care unit (PACU) patients were found in the severe obesity group no more than the non-obesity group. Significantly increased anesthesia puncture times for 5 > n ≥ 3 and n ≥ 5 were obtained in the morbid obesity group ( P = .0001 and P = .0001, respectively), with more patients in the puncture sitting position, compared with the non-obesity group ( P = .0001). Conclusion: GA, EA, and CSEA are safe and effective in severely or morbidly obese patients. Morbidly obese parturient show increased likelihood for fetal distress, PACU, sitting position puncture, puncture difficulty, and other pregnancy complications. There were more anesthesia puncture times in morbidly obese patients. Abstract : Supplemental Digital Content is available in the text